Sleep Apnea-Related Hypoxemia Predicts Post-Stroke Disability Better Than Apnea-Hypopnea Index - Tho Dinh Phung; Giap Van Vu; Dung Viet Nguyen; Hoai Thi Thu Nguyen (Sleep Medicine Research)
Background and Objective Sleep apnea affects two-thirds of acute ischemic stroke (AIS) patients, but its prognostic utility remains debated. This study evaluates nocturnal hypoxemia metrics and traditional sleep apneic indices as predictors of post-stroke functional outcomes. Methods This prospective cohort study enrolled patients with AIS at the Stroke Center of Bach Mai Hospital between April and October 2024. Participants underwent overnight cardiorespiratory polygraphy. Functional outcomes (modified Rankin Scale [mRS]) were evaluated at 3 months. Multivariate logistic regression analysis identified predictors of unfavorable outcomes (mRS >1). Results Of the 125 AIS patients enrolled (median National Institutes of Health Stroke Scale [NIHSS] score 3, interquartile range 2–4), 66.4% were diagnosed with sleep apnea (apnea-hypopnea index [AHI] >10). At 3-month follow-up, univariate analysis revealed that younger age, absence of diabetes, lower baseline NIHSS, absence of early neurological deterioration (END), lower AHI, reduced oxygen desaturation index (ODI), higher mean SpO2, and shorter percentage of time with SpO2 <90% were significantly associated with favorable functional outcomes (all p<0.05). In multivariate logistic regression, NIHSS, END, diabetes, ODI, percentage of time with SpO2 <90%, and mean SpO2 were independent predictors of unfavorable outcomes (all p<0.05). Notably, AHI did not show a significant association with outcomes (p>0.05). Conclusions NIHSS, END, diabetes, and nocturnal hypoxemia—not AHI—independently predict post-stroke disability. Hypoxemia duration (ODI, % time SpO2 <90%) offers superior prognostic value, advocating for sleep apnea management strategies targeting hypoxia mitigation.